Mind the gap - International comparison of cyclical adjustment of the budget - Gábor P. Kiss; Gábor Vadas (Magyar Nemzeti Bank, 2005)
Cyclically adjusted budget balance (CAB) is a widely cited and widely used concept in the evaluation of fiscal situations. The key idea behind it involves the identification of potential levels of economic variables. There are two recently used methods: the aggregate approach and the unconstrained disaggregate approach. In this paper we apply them on USA, Japan and 25 EU member countries to demonstrate that both approaches could be the source of considerable bias. While the aggregate approach cannot cope with different shocks, the unconstrained disaggregate method involves systematic bias and do not contain theoretical consideration. In order to avoid these distortions we present an alternative framework, which is able to incorporate the advantages of both approaches. Combining arbitrary output gap and constrained multivariate HP filter induces theoretically motivated disaggregation where we also exploit the implication of production function parameterisation. We found that the price effect resulting from the composition effect of different deflators could play an important role in evaluation of the fiscal position. To display the importance of composition effect we analyse the cyclical components of Finnish, Hungarian and Italian budget balances more in detail.
Keywords: H62; E32; 330; cyclically adjusted budget deficit; price gap; business cycles; constrained multivariate HP filter; Antizyklische Finanzpolitik; Konjunktur; Haushaltsdefizit; Aggregation; Schätzung; Finnland; Ungarn; Italien; EU-Staaten; USA; Japan